Tourism Finance: Investing and Financing in Sustainable Tourism - John Francis T. Diaz; Dang Trung Kien (Magister Manajemen, Program Pascasarjana, Universitas Warmadewa, 2019)
This study addresses the big problem that tourism projects and initiatives are encountering. Lack of financing is a common challenge hindering the development of tourism, resulting to a number of popular destinations that are slowly dying (e.g. the Great Wall of China, and the Angkor Wat). The purpose of Tourism Finance is to set criteria on which value-adding tourism projects should receive investment funding; and to evaluate a tourism organization’s financial needs to better decide on what capital structure (i.e., debt and/or equity) to appropriately raise to minimize the weighted average cost of capital. The method of this research is using qualitative research method with techniques of data collection by literature study and that were conducted by discussing seven potential sources of travel and tourism financing. Output, the result of this research is recommendations for leader in travel and tourism in improving the performance of tourism finance, investments to maintain the financial sustainability of organizations (i.e., business, non-profit and government) involved in the travel and tourism sectors.